2014
DOI: 10.1152/japplphysiol.00090.2014
|View full text |Cite
|
Sign up to set email alerts
|

Two years of combined high-intensity physical training and heat acclimatization affect lymphocyte and serum HSP70 in purebred military working dogs

Abstract: Military working dogs in hot countries undergo exercise training at high ambient temperatures for at least 9 mo annually. Physiological adaptations to these harsh conditions have been extensively studied; however, studies focusing on the underlying molecular adaptations are limited. In the current study, military working dogs were chosen as a model to examine the effects of superimposing endurance exercise on seasonal acclimatization to environmental heat stress. The lymphocyte HSP70 profile and extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 45 publications
(62 reference statements)
1
32
0
Order By: Relevance
“…In the current setup, median eHSP72 levels were significantly higher than the normal reference range observed in dogs at all-time points (Bruchim et al 2014). The reference range used in this study was based on our previous study using military working dogs, before initiation of physical training and exposure to high environmental temperatures.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In the current setup, median eHSP72 levels were significantly higher than the normal reference range observed in dogs at all-time points (Bruchim et al 2014). The reference range used in this study was based on our previous study using military working dogs, before initiation of physical training and exposure to high environmental temperatures.…”
Section: Discussionmentioning
confidence: 66%
“…We have shown that lymphocyte HSP72 protein levels and lymphocyte HSP72 mRNA are detectable and accurately measurable in working military dogs. In addition, in acclimated trained dogs, basal eHSP72 levels were higher than in naïve dogs, with significantly higher post-exercise levels in the acclimated dogs (Bruchim et al 2014). To the best of our knowledge, eHSPs levels have never been assessed in naturally occurring heatstroke patients.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Other studies have also observed that team-sport athletes participating in preseason (Racinais et al, 2014), in-season (Buchheit et al, 2011), and off-season (heat and altitude; Buchheit et al, 2013) training camps in the heat (∼34°C) improve performance by 7% and 44% (Yo-Yo Intermittent Recovery test level 1 and 2, respectively) in temperate conditions (∼22°C). The mechanisms modulating the transfer between hot and cool conditions could be linked to a variety of ergogenic responses, with cardiovascular/ thermoregulatory and cellular (Bruchim et al, 2014) adaptations. As recently highlighted by Corbett et al (2014), heat acclimation may provide a stimulus for improving performance in nonthermally challenging environments via improvements in VO 2max , lactate threshold, and economy.…”
Section: Performance In Cool Environmentmentioning
confidence: 99%